Roles of coal gasification wastewater in coal electrolysis for hydrogen production. (1st December 2021) - Chen, Cong; Liu, Jianzhong; Wu, Hongli; Wang, Jianbin; Cheng, Jun
Abstract: Coal-assisted water electrolysis can reduce the electricity consumption of traditional water electrolysis by 40–60%, but the rate of hydrogen production in this process is very slow. Some coal gasification wastewater can promote the electrical oxidation of coal, the addition of which can achieve resource utilization of wastewater while producing hydrogen at low cost. In this study, the electrolysis characteristics and oxidation mechanism of gas washing water are studied using anode reaction kinetics, and its role in the process of coal electrolysis is studied. The results show that the main anodic reactions of gas washing water are, in order of increasing voltage, the oxidation of organic matter, bromide ions, and the water decomposition reaction, and that there is no obvious interaction between these three oxidation stages and Fe 3+ /Fe 2+ . On the one hand, gas washing water can promote the catalysis of iron ions and increase the effective iron concentration in the solution. On the other hand, it plays an important role in changing the surface state of coal particles and improving the electrochemical activity of coal, thereby increasing the reaction rate of coal electrolysis.